(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
The quality of environment must be measured by indicators and their critical values - criterions. The general indicators for evaluation degree of sustainability of environment were calculated: environment quality preserving indicator Vk and human quality requirements indicator Ck-As a result of analyse some situations in interrelations between human activities and environment were established the next important parameters: minimum level of human living quality aol energy of human activities - Q; capacity of standard environment quality - b; intensity of lose environment quality a and optimization coefficient of human living standards L. It is possible to regulate parameters Q and a for obtaining sustainability in region.Paper presents particular indicators for urbanoecosystems. Indicators were calculatedfor evaluation of air, water and territory pollution.